2022
DOI: 10.3390/ijms232113585
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Disruption of Lats1 and Lats2 in Mice Impairs Testis Development and Alters Somatic Cell Fate

Abstract: Hippo signaling plays an essential role in the development of numerous tissues. Although it was previously shown that the transcriptional effectors of Hippo signaling Yes-associated protein (YAP) and transcriptional coactivator with PDZ-binding motif (TAZ) can fine-tune the regulation of sex differentiation genes in the testes, the role of Hippo signaling in testis development remains largely unknown. To further explore the role of Hippo signaling in the testes, we conditionally deleted the key Hippo kinases l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 83 publications
0
8
0
Order By: Relevance
“…In the latter, disorganized larger tubules are also present but never become sufficiently large to fuse with each other. 30 However, inactivation of Lats1/2 is not limited to the Sertoli cells in L1;L2;Nr5a1 mice, as inactivation also occurs in the Leydig cells. Lats1/2 inactivation in Leydig cells leads to their transdifferentiation into myofibroblast-like cells and the secretion by these cells of a collagen-based extracellular matrix into the interstitial space.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In the latter, disorganized larger tubules are also present but never become sufficiently large to fuse with each other. 30 However, inactivation of Lats1/2 is not limited to the Sertoli cells in L1;L2;Nr5a1 mice, as inactivation also occurs in the Leydig cells. Lats1/2 inactivation in Leydig cells leads to their transdifferentiation into myofibroblast-like cells and the secretion by these cells of a collagen-based extracellular matrix into the interstitial space.…”
Section: Discussionmentioning
confidence: 99%
“…The specification of Sertoli cell fate and their proper differentiation throughout testis development require the action of the transcription factors SRY and SOX9 as well as the action of autocrine factors such as FGF9, PGD2, AMH, and Activin B. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] Although these autocrine factors and the signaling pathways they activate are essential for fetal Sertoli cell differentiation, our previous work has demonstrated that additional signaling pathways, such as Hippo signaling, 29,30 can fine-tune these processes. However, this is the first report to thoroughly evaluate the role of Hippo signaling and Lats1/2 specifically in the developing Sertoli cells.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations